2013
DOI: 10.1172/jci73313
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor RUNX1 promotes survival of acute myeloid leukemia cells

Abstract: The accession numbers for the antibody nucleotide sequences were incorrectly noted in Methods. The correct sentence appears below.Antibody nucleotide sequences have been deposited in GenBank (JX458933-52); antibody X-ray structure has been deposited in the Protein Data Bank (4GSD).The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…By contrast, deactivating the RUNX1 gene may cause amplification of myeloid progenitors and the subsequent development of AML. A previous study undertaken by Silva et al (25) suggested that the RUNX1 gene acts as a classical tumor suppressor gene; however, other studies have suggested that RUNX1 functions as an oncogene and that it may cause AML development due to its pro-survival role in leukemia cell proliferation (27)(28)(29)(30). The results of these studies also suggested that the prognostic impact in CN-AML depends on the RUNX1 expression level.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…By contrast, deactivating the RUNX1 gene may cause amplification of myeloid progenitors and the subsequent development of AML. A previous study undertaken by Silva et al (25) suggested that the RUNX1 gene acts as a classical tumor suppressor gene; however, other studies have suggested that RUNX1 functions as an oncogene and that it may cause AML development due to its pro-survival role in leukemia cell proliferation (27)(28)(29)(30). The results of these studies also suggested that the prognostic impact in CN-AML depends on the RUNX1 expression level.…”
Section: Discussionmentioning
confidence: 94%
“…The results of these studies also suggested that the prognostic impact in CN-AML depends on the RUNX1 expression level. A study undertaken by Goyama et al (28) reported that overexpression of the RUNX1 gene inhibited the growth of regular cord blood cells by inducing myeloid differentiation. It was suggested that the RUNX1 gene may be a valuable novel marker for risk stratification in patients with AML and that it is an excellent candidate for anticancer-targeted therapy due to the modulation of its post-translational modifications (29).…”
Section: Discussionmentioning
confidence: 99%
“…In general, RUNX1 mutations are considered to result in the loss of RUNX1 functions. On the other hand, recent several reports indicate that wild-type RUNX1 is also important for growth and survival of leukemia cells [16].…”
Section: Abstract Runx1 · Fpd/aml · Fpd/mm · Germ Line Mutationmentioning
confidence: 99%
“…These data show that RUNX1-ETO and 1 3 RUNX1 are in balance with each other, and additional studies have shown that each regulate distinct sets of genes which are both required to keep AML cells alive [127]. This dependency on the wild-type copy of RUNX1 has also been demonstrated for other RUNX1 and CBF translocations [127,128]. Genome-wide binding studies have shown that RUNX1-ETO binds to thousands of genes in chromatin [122,125].…”
Section: Runx1 and Pu1 In Amlmentioning
confidence: 57%